CLINICAL PROFILE OF PATIENTS HAVING SUBCLINICAL AND CLINICAL HYPOTHYROIDISM ATTENDING GENERAL MEDICINE OPD OF A TERTIARY CARE MEDICAL CENTER - BASAVARAJ GT; VISHWANATH SAJJANSHETTY; SHARANABASAPPA B NANDYAL (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to analyze and compare the clinical profile of patients having clinical and subclinical hypothyroidism. Methods: This was a comparative observational study in which adult patients with clinically overt and subclinical hypothyroidism were included on the basis of predefined inclusion and exclusion criteria. Written and informed consent was obtained from all the patients. Demographic details such as age gender and occupation were noted. The normal reference values of T3, T4, and TSH for diagnosis of subclinical and clinical hypothyroidism were taken to be 0.8–2 ng/mL, 5.5–12.2 μg/dL, and 0.3–4.5 μIU/mL. The cases were divided into two groups, namely, Group C (clinical hypothyroidism) and Group SC (Subclinical hypothyroidism). Mean T3, T4, and TSH levels and clinical signs and symptoms were compared in both the groups. SSPS 21.0 software was used for statistical analysis and p<0.05 was taken as statistically significant. Results: In cases of clinical hypothyroidism out, there were 42 (70%) females and 18 (30%) males, whereas in cases of subclinical hypothyroidism, there were 38 (63.33%) females and 22 (36.67%) males. There was an overall female preponderance in both the groups. The mean age of patients in group C was found to be 39.48±12.36 whereas the mean of patients in SC group was found to be 42.82±13.46. The mean T3 and T4 were low in clinical hypothyroidism and mean TSH levels were high and the difference was statistically highly significant (p<0.0001). In cases with clinical as well subclinical hypothyroidism, the most common clinical features were dry skin, fatigue, and cold intolerance. The prevalence of fatigue, weight gain, cold intolerance, dry skin, pedal edema, and thyroid swelling was more in patients with clinical hypothyroidism as compared to the patients with subclinical hypothyroidism and the difference was found to be statistically significant. Conclusion: The clinical presentation of clinical as well as subclinical hypothyroidism varies and a high index of suspicion is necessary for the diagnosis particularly in cases of subclinical hypothyroidism so that appropriate interventions can be undertaken.